Aneurysms of the ascending aorta and arch: the role of imaging in diagnosis and surgical management. (January 2011) - Bonnichsen, Crystal R; Sundt III, Thoralf M; Anavekar, Nandan S; Foley, Thomas A; Morris, Michael F; Martinez, Matthew W; Williamson, Eric E; Glockner, James F; Araoz, Philip A
Thoracic aortic aneurysms tend to be asymptomatic and were previously often diagnosed only after a complication such as dissection or rupture occurred. Better imaging techniques and an increase in the use of cross-sectional imaging has led to an increase in the diagnosis of aortic aneurysms, which has allowed for elective treatment prior to the development of a complication. The location, size and etiology of an aneurysm all impact the clinical outcomes and these factors are used to determine the appropriate timing of surgical replacement. Surgeons often rely on the information obtained from preoperative imaging to determine when to intervene and what type of procedure will be necessary, making it important for the radiologist to understand these issues in order to provide the necessary information. Postoperative imaging after surgical replacement of the aorta is also important, as there are some common findings that occur in this patient population that can impact how they are treated. The purpose of this article is to review the etiology and associated findings of aneurysms of the ascending aorta and arch, with a focus on how computed tomography angiography and magnetic resonance angiography findings are used to determine the appropriate timing for elective replacement and the type of surgical procedure, as well as the role of follow-up imaging. This will include a review of the most commonly performed types of surgical procedures, to provide an understanding of how the findings of preoperative imaging studies impact what the surgeon does in the operating room, as well as the expected findings of postoperative imaging studies.